Deposition of SiOx thin films using hexamethyldisiloxane in atmospheric pressure plasma enhanced chemical vapor deposition. (April 2020) - Krueger, T; Hansen, L; Kersten, H
Abstract: The atmospheric pressure plasma enhanced chemical vapor deposition method was used to study the enhancement of the particle growth and thin layer deposition. For this purpose, an atmospheric pressure plasma jet was used to deposit silicon oxide compounds on a (100)-silicon wafer substrate. In this parametric study, hexamethyldisiloxane (HMDSO) was dissociated under different plasma jet parameters. It was found that by varying the working gas, the treatment time and jet parameters, such as nozzle-to-substrate distance and input energy, it is possible to influence the particles size and the morphology of the thin film. The choice of the working gas plays a major role in the formation of nanoparticles and the surface texture. This study was focused on the particles growth and how the growth can be controlled by tuning the parameters mentioned. Particles size of up to 100 nm was achieved under optimized conditions.